ANALISIS KONSEP HAK ASASI MANUSIA DALAM BUKU TEKS PPKn UNTUK MEMBENTUK KARAKTER SISWA (Analisis Deskriptif Siswa Kelas XI SMA di Kota Bandung) - Nuryadi, Aim Abdulkarim, Prayoga Bestari (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2016)
Indonesia is a country that has diversity, both in language, culture, ethnicity, religion or skin color. Supposedly this difference makes Indonesia the country into a peaceful, prosperous, and free from suffering. Therefore, dipersekolahan already must teach about the importance of human rights. Dibelajarkan human rights material in civics intended as an effort to increase students' knowledge and awareness of human rights. The aim is to prevent students from doing acts contrary to human rights and discriminatory behavior based on differences resulting human rights violations. Human rights violations are not only usually carried out by local police officers, the public can commit human rights violations are severe.Generally, this study aimed to describe the analysis of human rights concepts in textbooks PPKn to shape the character of the students. In particular, this study aims to test and find the relationship of human rights concepts and attitudes implement values-based character PPKn textbook to shape the character of students. This study uses a quantitative approach with descriptive analysis research method. Sources of data in this study were teachers and students of class XI High School in Bandung and documents. Techniques of collecting data using interviews, observations, questionnaires, and documentation. Data analysis procedures consisted of normality test, descriptive analysis, multiple correlation analysis, data display, and inference data. The results showed that a) The concept of human rights in textbooks PPKn presented not only focuses on the acquisition of cognitive, but also includes the development of attitudes and behavior of students. b) The attitude of the students in carrying out the character values must emerge from consciousness so that it can be implemented, both in the family, school and community; and c) The concept of human rights in textbooks dealing PPKn very powerful in shaping the character of students.